Green synthesis of silver nanoparticles using Magnolia alba leaf extracts and evaluating their antimicrobial, anticancer, antioxidant, and photocatalytic properties - Shaveen De Mel; Juliana Gruenler; Logan Khoury; Ashton Heynes; Julianne Fazekas; Kendra Damaske; Thushara Galbadage; Richard S. Gunasekera; Ross S. Anderson (Scientific Reports)
Abstract The biosynthesis of silver nanoparticles has recently emerged as a promising approach in nanomedicine, particularly for targeted therapeutic applications. Green synthesized (plant-based) nanoparticles have been shown to offer enhanced reduction efficiency, greater bioavailability, and improved stability compared to synthetic nanoparticles. Here, we report the green synthesis of silver nanoparticles (AgNPs) using Magnolia alba leaf extract (MLE). The formation of these Magnolia-derived silver nanoparticles (MAgNPs) was verified through UV–Vis spectroscopy with a surface plasmon resonance peak at 440 nm, and further characterized by scanning electron microscopy, which showed that the MAgNPs have a mean diameter of 40 nm and a spherical morphology. MAgNPs exhibited significant antibacterial activity against Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Enterococcus faecalis, methicillin-resistant and -sensitive Staphylococcus aureus, with a minimum inhibitory concentration of 0.00043 mg/mL and a minimum bactericidal concentration of 0.00043 mg/mL and 0.0017 mg/mL, respectively. Disc diffusion and plaque assays with MAgNPs demonstrated strong antifungal activity against Candida albicans, with a zone of inhibition of 14 mm, and antiviral activity against T7 bacteriophage (p = 0.0004). In vitro studies with HCT-116 human colon cancer cells, MAgNPs exhibited bi-phasic, dose-dependent inhibition of viability with a 20–40% reduction, surpassing the positive control Camptothecin. Antioxidant assays indicated that MAgNPs showed significantly higher antioxidant activity compared to MLE, with enhanced Total Flavonoid Content (p = 0.0066), Total Phenol Content (p = 0.0013), and Total Antioxidant Capacity (p = 0.0051). Additionally, MAgNPs showed efficient photocatalytic degradation of the azo bond in methyl orange within 30 min. To our knowledge, this is the first report on the biosynthesis of MAgNPs and their multifunctional properties, highlighting the promise of MAgNPs in biomedical and environmental fields.